DOMESTIC AND FOREIGN BANKSâ STABILITY IN INDONESIA: THE GREY ZONE TRAP AND KEY DETERMINANTS - Purnawan, Vanessa
The recent global financial crisis in 2008 has comprehensively predisposed the stability of most banking sectors all over the world, but apparently not in Indonesia. Reported by IMF in 2010, Indonesian banking industry showed such a remarkable resiliency level in terms of stability endurance during and after the negative shocks. Credit, interest rate, and liquidity risks proved to be less vulnerable, cushioned by a high capital and earnings buffer against macroeconomic volatility. Investors and policy-makers in Indonesia seemed to be rejoiced about its healthy banking system which allegedly have ameliorated in significant way since the reformation era. Openness of foreign banks’ participation since 1998 potentially had strengthen the overall financial stability in the respective host country facing the crisis. Thus, a noteworthy question persists, whether Indonesian domestic banking sectors are truly withstood towards financial crisis or perchance the foreign-owned banks are the ones which contribute to the outstanding stability performance of Indonesian banking sector during the economic turbulence. Hence, this paper investigates the sustainability level of domestic banks and foreign banks in Indonesia to the crisis effect by using Z-score modification model as banks’ stability indicator. The research is based on the aggregate data of Indonesian foreign and domestic banks from the year of 2005 to 2015. The proceed lays among the bankruptcy zone, safe zone, or grey zone which considered as a high alert partial safe zone. It shows that the domestic banking sector in Indonesia could not jump out of the grey zone in a decade unlike the foreign banks, which since 2008, have entered safe zone area and shown increasing performance in terms of stability level. In addition, this study also assesses the main constituents which imparts the stability levels of both foreign and domestic banks by applying VECM or Vector Error Correction Model of microprudential indicators using and macroeconomics indicators, such as GDP, inflation, and exchange rate return. From the result of the VECM, it is discovered that the domestic banking sector was bridled of the grey zone due to its incommensurate loan control, inefficiency in generating profitability and liquidity from assets, and lack of capital buffer’s presence. Nevertheless, the findings also reveal that neither of the domestic nor foreign banks in Indonesia was completely safe against credit risk. Hence research towards remedial measures for minimizing negative effects on the financial health of both of the banks, particularly the domestic banking sector is essential to ensure its sustainability towards crisis.